STUDI KOMPARATIF MODEL PEMBELAJARAN KOOPERATIF TIPE NHT DAN STAD TERHADAP HASIL BELAJAR IPS SISWA KELAS V SDN SUKOWIDI 01 DAN SDN SUKOWIDI 02 KECAMATAN NGUNTORONADI DI KABUPATEN MAGETAN TAHUN PELAJARAN 2015/2016 - Arni Gemilang Harsanti (Universitas Muhammadiyah Semarang, 2017)
The subject of Social Sciences is an integrated subject of several social science subjects formulated on the basis of reality and social phenomena organized and presented scientifically and psychologically for educational purposes. In the learning process IPS often found the value of student learning outcomes are still low. Teachers need an application of varied learning models in order to improve IPS learning outcomes.This research is a quantitative research with type of experimental research method using post-test design of two random subject subjects. This design is one of the simplest designs in experiments and the most powerful of all experimental designs. Two randomly selected subjectgroups, each placed in different conditions. Technique of collecting data by using test. Data analysis using statistical method with t-test formula. Based on the t test obtained tcount = 5.194 and ttable = 1.725, thus thitung> ttable, then in accordance with the calculation criteria indicates that H1 received and H0 rejected. Based on the calculation can be seen that there are significant differences between students who were taughtusing NHT (Number Head Together) learning model and students taught using STAD learning model (Student Team Achievement DivisionKeywords: NHT (Number Head Together), STAD (Student Team Achievement Division), Learning Results IPS